Subjects with chronic lymphocytic leukaemia‐like B‐cell clones with stereotyped B‐cell receptors frequently show MDS‐associated phenotypes on myeloid cells. (24th September 2014) - Rodríguez‐Caballero, Arancha; Henriques, Ana; Criado, Ignacio; Langerak, Anton W.; Matarraz, Sergio; López, Antonio; Balanzategui, Ana; González, Marcos; Nieto, Wendy G.; Cortesão, Emília; Paiva, Artur; Almeida, Julia; et al.
Summary An increasing body of evidence suggests the potential occurrence of antigen encounter by the cell of origin in chronic lymphocytic leukaemia (CLL) and CLL‐like monoclonal B‐cell lymphocytosis (MBL). However, the scenario in which this event might occur remains unknown. In order to gain insight into this scenario we investigated the molecular, cytogenetic and haematological features of 223 CLL‐like (n = 84) and CLL (n = 139) clones with stereotyped (n = 32) versus non‐stereotyped (n = 191) immunoglobulin heavy chain variable region (IGHV) amino acid sequences. Overall, stereotyped CLL‐like MBL and CLL clones showed a unique IGHV profile, associated with higher IGHV1 and lower IGHV3 gene family usage (P = 0·03), longer IGHV complementary determining region 3 (HCDR3) sequences (P = 0·007) and unmutated IGHV (P < 0·001) versus non‐stereotyped clones. Whilst the overall size of the stereotyped B‐cell clones in peripheral blood did not appear to be associated with the CLL‐related cytogenetic profile of B‐cells (P > 0·05), it did show a significant association with the presence of myelodysplastic syndrome (MDS)‐associated immunophenotypes on peripheral blood neutrophils and/or monocytes (P = 0·01). Altogether our results point to the potential involvement of different selection forces in the expansion of stereotyped vs. non‐stereotyped CLL and CLL‐like MBL clones, the former being potentially favoured by an underlying altered haematopoiesis.